Efficient Hydrogen Generation From Hydrolysis of Sodium Borohydride in Seawater Catalyzed by Polyoxometalate Supported on Activated Carbon - Xi, Senliang; Wang, Xiaojun; Wu, Dan; Hu, Xingtao; Zhou, Shixue; Yu, Hao (Frontiers in Chemistry, 2020)
Phosphotungstic acid (HPW) as a polyoxometalate was selected as the active component of the catalyst. The activated carbon supported different percentage of HPW catalysts were prepared by impregnation and were characterized by X-ray diffraction (XRD), nitrogen adsorption, Fourier transform infrared (FTIR), and scanning electron microscope (SEM). The results showed that the phosphotungstic acid retained the original Keggin structure after being supported on activated carbon, the specific surface of the HPW/C was much bigger than that of pure HPW. The catalytic performance of HPW/C in the hydrogen generation reaction by hydrolysis of sodium borohydride in seawater and in deionized water were studied. 2.5 wt.% HPW/C showed the fastest hydrolysis reaction rate and the biggest volume of hydrogen generated. As for hydrolysis of sodium borohydride, catalytic effect of HPW/C was better in seawater than in distilled water. Phosphotungstic acid dispersed on activated carbon is a real promising catalytic system for the development of hydrogen generation by hydrolysis of NaBH4 in seawater.